THE ASSESSMENT OF THE ENVIRONMENTAL SITUATION AT THE TERRITORY OF THE DARNYTSYA INDUSTRIAL AREA OF THE KYIV CITY - Radomska, Margaryta Myroslavivna; Ryabchevsky, Oleg Volodymyrovych; Chaplygina, Olexandra Viktorivna (Science-based technologies, 2019)
The condition of urban ecosystems is strongly dependant on many factors, including population density, efficiency of municipal services provision and level of technogenic pressure. The major sources of negative impacts at urban territories on the environment are industrial zones. Due to decreasing efficiency of industrial zones exploitation and reduced business activity they are considered a liability demanding managerial solutions. The current trends for revitalization of cities, especially urban industrial zones, have been discussed. The most typical directions of industrial zones transformation is residential districts, recreational areas, entertaining and shopping centers. The need for the analysis of environment condition at the territory prior to its refurbishing is substantiated by the necessity to prevent population health risks. The impacts of the Darnytsya industrial zone on the adjoined territory have been studied separately for major environment components. The sources of environment pollution here are Darnytsky car-repair plant, tank repair plant, pharmaceutical factory, railway depot, depot of subway, depot of trams and silk factory. The analysis has showed the considerable level of air pollution, but it is mostly conditioned by traffic, while soils are polluted with heavy metals, due to long term industrial activity at the territory. The green infrastructure of the affected area is in normal condition, especially residuals of natural forest phytocenosis. The state of water bodies is satisfactory, but with clear tendency to degradation. It is offered to include one of the lakes into the network of protected areas to prevent further quality reduction and conduct the information campaign on encourage local population to careful use of recreational resources at the territory. The project of the Darnytsky industrial area renovation and transformation to residential district or service center must include the soil remediation and maintenance of water objects.